Bioavailability and pharmacokinetic profile of balovaptan, a selective, brain-penetrant vasopressin 1a receptor antagonist, in healthy volunteers. (3rd August 2021) - Derks, Michael; Lennon-Chrimes, Sian; Guenther, Andreas; Squassante, Lisa; Wandel, Christoph; Szczesny, Piotr; Paehler, Axel; Kletzl, Heidemarie
ABSTRACT: Background: Balovaptan is a potent, selective vasopressin 1a receptor antagonist. The early-phase pharmacokinetics (PK) of balovaptan are reported. Research design and methods: Two Phase 1 studies (overall N = 93) assessed single- and multiple-dose balovaptan PK in healthy adults. One ( N  = 16) assessed absolute oral bioavailability (10 mg or 50 mg) vs a [ 13 C]-balovaptan microdose. The other ( N  = 77) explored single- (0.5–76 mg) and multiple-dose (14 days; 12–52 mg/day) – randomized 6:2 balovaptan:placebo per dose – PK, dose proportionality, and the effect of food on single-dose (32 mg) Cmax and AUCinf . Results: Absolute balovaptan bioavailability was high (103–116%). Steady-state (Day 14) balovaptan PK was approximately dose proportional with a half-life of 45–47 hours, but single-dose Cmax increased more than dose proportionally and half-life was inversely dose-proportional – a discordance partially attributable to a dose-and-time-dependent volume of distribution. Accumulation (Day 1–Day 14) was inversely dose-proportional (~3.5 [12 mg] to ~1.8 [52 mg]). There was no relevant effect of a high-fat meal on single-dose balovaptan exposure. There were no safety signals: 2/93 subjects discontinued for adverse events. Conclusions: Balovaptan was well tolerated at single (≤76 mg) and multiple (≤52 mg/day) doses, with a PK profile supportive of once-daily administration without food restrictions. Trial registration: ClinicalTrials.gov NCT03764449; NCT01418963.